2018
DOI: 10.1186/s12992-018-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

The Improving Global Health fellowship: a qualitative analysis of innovative leadership development for NHS healthcare professionals

Abstract: BackgroundThe importance of leadership development in the early stages of careers in the NHS has been highlighted in recent years and many programmes have been implemented which seek to develop leadership skills in healthcare professionals. The Improving Global Health (IGH) Fellowship scheme is one such programme, it provides a unique leadership development opportunity through an overseas placement with a focus on quality improvement work. This evaluation examines the impact of completing an IGH Fellowship on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…27 Other objective outcomes included reduced organisational turnover of participants, 28 improved departmental working climate, 39 reduced sick leave 44 and increased promotion of women. 45 Organisational outcomes were subjectively indicated through reports of increased staff retention 56 and improvement in organisational effectiveness. 27 One study reported that 'intangible benefits' resulted in a 106% financial ROI.…”
Section: Behavioural and Organisational Outcomes In Higher Reliabilitmentioning
confidence: 99%
“…27 Other objective outcomes included reduced organisational turnover of participants, 28 improved departmental working climate, 39 reduced sick leave 44 and increased promotion of women. 45 Organisational outcomes were subjectively indicated through reports of increased staff retention 56 and improvement in organisational effectiveness. 27 One study reported that 'intangible benefits' resulted in a 106% financial ROI.…”
Section: Behavioural and Organisational Outcomes In Higher Reliabilitmentioning
confidence: 99%
“…In hindsight, the leadership skills questionnaire for senior colleagues should have been completed at baseline and after the Fellowship to reflect answers more accurately. In comparison with other global health Fellowships [ 8 ], the number of participants included was small and the time spent in the partnership country was limited. Tools that elicit self-reported attainment and behaviour changes are considered to provide weak evaluation evidence, are of variable accuracy [ 33 ] and most studies use unvalidated tools.…”
Section: Limitationsmentioning
confidence: 99%
“…A total of 12 health partnerships were formed between multidisciplinary teams from institutions in the UK, including NHS Trusts, together with institutions in Ghana, Tanzania, Uganda, and Zambia. These partnerships were created to allow ideas and knowledge exchange to further develop innovative ways to tackle the problem of AMR and raise awareness, which will mutually benefit the UK and low-to-middle-income countries (LMICs) [ 8 , 9 ]. Success of the CwPAMS projects was dependent on strong leadership and project management within each partnership.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists in the UK as part of the projects then linked directly with pharmacists in African countries to support their colleagues in Africa. Traditionally, volunteer opportunities in global health involve spending prolonged time in a country, and improvements are not always sustainable when the volunteer(s) leave [ 8 ]. As a novel approach with a strong focus on the pharmacy profession, pharmacists in the UK with limited funding and restricted time focused on building the capacity of pharmacists in Ghana, Uganda, Tanzania and Zambia in order to develop sustainable antimicrobial stewardship interventions.…”
Section: Introductionmentioning
confidence: 99%